The neutrophil to lymphocyte ratio in heart failure: a comprehensive review - Delcea Caterina; Buzea Cătălin Adrian; Dan Gheorghe Andrei (Sciendo, 2019)
Introduction. Heart failure (HF) and systemic inflammation are interdependent processes that continuously potentiate each other. Distinct pathophysiological pathways are activated, resulting in increased neutrophil count and reduced lymphocyte numbers, making the neutrophil to lymphocyte ratio (NLR) a potential indirect marker of severity. We conducted this comprehensive review to characterize the role of NLR in HF.